2012
DOI: 10.1371/journal.pone.0045886
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the Detailed Structure of Cortical and Thalamic Neurons in the Adult Rat Brain with Refined Biotinylated Dextran Amine Labeling

Abstract: Biotinylated dextran amine (BDA) has been used frequently for both anterograde and retrograde pathway tracing in the central nervous system. Typically, BDA labels axons and cell somas in sufficient detail to identify their topographical location accurately. However, BDA labeling often has proved to be inadequate to resolve the fine structural details of axon arbors or the dendrites of neurons at a distance from the site of BDA injection. To overcome this limitation, we varied several experimental parameters as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…tracers such as horseradish peroxidase (HRP), Phaseolus vulgaris leucoagglutinin (PHA-L), and biotinylated dextran amine (BDA; Gerfen and Sawchenko, 1984;Glover et al, 1986). Among these, BDA currently is widely used as an anterograde tracer because of its experimental flexibility (Lanciego and Wouterlood, 2011;Ling et al, 2012). BDA is well validated and has been used to study the connectivity of a variety of brain regions across many different species, such as macaque (Tanigawa et al, 2005), rat (Thompson and Swanson, 2010), and mouse (Wang and Burkhalter, 2007;Wang et al, 2012).…”
mentioning
confidence: 99%
“…tracers such as horseradish peroxidase (HRP), Phaseolus vulgaris leucoagglutinin (PHA-L), and biotinylated dextran amine (BDA; Gerfen and Sawchenko, 1984;Glover et al, 1986). Among these, BDA currently is widely used as an anterograde tracer because of its experimental flexibility (Lanciego and Wouterlood, 2011;Ling et al, 2012). BDA is well validated and has been used to study the connectivity of a variety of brain regions across many different species, such as macaque (Tanigawa et al, 2005), rat (Thompson and Swanson, 2010), and mouse (Wang and Burkhalter, 2007;Wang et al, 2012).…”
mentioning
confidence: 99%
“…In previous studies, it has shown that BDA labeling appeared as early as 3 days and remained unchanged up to 14 days after injection in rats (Rajakumar et al, 1993). In contrast, recent study indicated that the quality of BDA labeling could be changed in animals following the different post-injection survival time (Ling et al, 2012).…”
Section: Time-related Morphological Changes Of Bda Labelingmentioning
confidence: 95%
“…The use of the biotinylated dextran amine (BDA) is a common technique for neural pathway tracing in the central nervous system (Reiner et al, 2000;Veenman, Reiner, & Honig, 1992). Although BDA can be transported rapidly from the injection site anterogradely and retrogradely to yield excellent neural labeling, the direction of BDA transportation is closely related to its molecular weight (Ling, Hendrickson, & Kalil, 2012;Reiner et al, 2000). In the family of BDA, high molecular weight BDA (10 kDa) seems to be prefererentially transported anterogradely, while low molecular weight BDA (3 kDa) retrogradely (Fritzsch, 1993;Kaneko, Saeki, Lee, & Mizuno, 1996;Ling et al, 2012;Medina & Reiner, 1997;Reiner et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations